On the need for narratives in patient information: Differentiating types and functions of narratives from pulmonary embolism patients' point of view - Kalch, Anja; Küchler, Constanze; Albani, Aliscia Rebecca; Bilandzic, Helena; Fischer, Simone; Kirchberger, Inge (Frontiers in Communication, 2022)
The inclusion of narratives in evidence-based patient information is a heavily discussed topic in literature. Narratives elicit intense engagement and emotional insights, but may also cause unintended persuasion effects. There is mixed evidence that adding narratives to non-narrative factual patient information is valuable for patients. In addition, providing patients with narratives about the outcome of treatments has been found to bias treatment decisions, in line with the direction implied by the narratives. This may counteract informed decision making of patients. However, narratives about the process of a treatment and personal experiences with treatments may support the well-being of patients in tertiary prevention. In order to investigate patients’ views on narratives and their function in patient information, we conducted 26 semi-structured qualitative interviews with pulmonary embolism patients. Answers were coded using thematic analysis. Results show that patients are especially interested in experience and process narratives when combined with evidence-based patient information. We identified four main functions of experience and process narratives that patients ascribe to these narratives: 1) motivating self-reflection and reflection on the recovery process, 2) reducing the feeling of loneliness, 3) reducing emotional distress and 4) inspiring mindful mastery.